Avaliação da capacidade funcional, nível de atividade física e qualidade de vida de adolescentes asmáticos - Basso, Renata Pedrolongo (Universidade Federal de São Carlos, 2009)
Data collected allowed the development of two studies, their objects are: Study I compare the physical performance, cardiovascular and respiratory responses, and the sensation of dyspnea (BorgDyspnea) and fatigue and pain in the lower limbs (BorgLL) between asthmatic and healthy adolescents in the six minute walking test (6MWT) and six minute step test (6MST); and determine the influence of body mass index (BMI), physical activity level (PAL) and spirometric variables in physical performance and responses obtained in the tests. Study II verify whether in 6MST there is a correlation between quality of life (QOL) in adolescents with asthma and the following variables: physical performance, cardiorespiratory responses, BorgDyspnea, BorgLL, spirometric responses. Also, whether there is a correlation between QOL and the PAL of these individuals. For this, 19 adolescents with asthma (AG) and 19 healthy (HG), aged between 11-15 years, both sexes, were assessed by spirometry, by 6MWT and by 6MST, and their PAL were quantified by International Physical Activity Questionnairy (IPAQ). The asthmatics answered the Pediatric Asthma Quality of Life Questionnaire (PAQLQ). In the Study I, in the 6MST, lower performance (6MST-T), lower heart rate (HR) and higher BorgLL were observed in AG. In the 6MWT, the walking distance (WD) was positively correlated with PAL, and HR with BMI in the AG; and in the HG, the HR and respiratory rate (RR) were positively correlated with WD. In the 6MST, in the AG, HR and RR were positively correlated with spirometric variables, and the PAL with 6MST-T. The 6MST-T was negatively correlated with BMI, and BorgDyspnea with PAL. In the HG, the HR and RR were positively correlated with spirometric variables; and the BMI with BorgLL. In Study II, negative correlations were obtained between BorgDypnea and total score of the questionnaire (PAQLQ-T); and BorgDyspnea and BorgLL with symptoms domain (St) and limitation in activities domain (LA). They were observed positive correlations between PAL and PAQLQ-T, LA and St. In the regression analysis, for PAQLQ-T and LA just BorgDyspnea was significantly in predicted them; and for St just BorgLL. Concluded that the 6MST was capable to detect the limitations of adolescents with asthma in activities of moderate intensity, because the AG showed lower physical performance and higher BorgLL in relation to HG. The spirometric variables, the BMI and the PAL influenced the responses obtained in the tests. Also, the higher PAL and lower BorgDyspnea and BorgLL in 6MST better quality of life. The 6MST has to be an option for evaluating exercise capacity in these asthamatics, because it reflects the discomfort caused by asthma, due to their symptoms, in the practice of physical activities of daily living.
Keywords: Asma; Teste de caminhada; Teste de degrau; Adolescentes; Qualidade de vida; Asthma; Walking; Step test; Adolescent; Quality of life; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL